The Influence Of Organizational Culture, Job Satisfaction, And Internal Communication On Employee Retention In Upt-Pam South Bangka Regency, Bangka Belitung Province - Ayu Ratnasari; Subiyanto, Didik; Tri Kusuma, Nala (Universitas Muhammadiyah Pontianak, 2026)
This study investigates the influence of organizational culture, job satisfaction, and internal communication on employee retention at UPT-PAM South Bangka. Using a quantitative approach with a saturated sample of 50 respondents, data were collected via a Likert-scale questionnaire and analyzed using PLS-SEM. The findings show that organizational culture has a positive but insignificant effect on retention. In contrast, job satisfaction and internal communication have significant positive effects and are dominant factors. The R² value of 0.750 indicates a strong model. These results suggest enhancing satisfaction and communication is essential for improving employee retention in public sector organizations. Keywords: Employee Retention, Organizational Culture, Job Satisfaction, Internal Communication, Public Sector, Human Resource Management, PLS-SEM, South Bangka